Correction: Partial Agonism of Taurine at Gamma-Containing Native and Recombinant GABAA Receptors. - Olaf Kletke; Guenter Gisselmann; Andrea May; Hanns Hatt; Olga A Sergeeva (PLoS ONE, 2013)
[This corrects the article DOI: 10.1371/journal.pone.0061733.].